A study on the appraisal practices of selected archives of government institutions in Metro Manila - Odilao, Angeline May I. (2009)
The study was conducted to know how appraisal is done in archives of government institutions in Metro Manila. It focused on appraisal practices in six selected archives which include the Legislative Records and Archives Service of the Senate of the Philippines (LRAS), Cultural Center of the Philippines Library and Archives (CCPLA), National Historical Institute Resource Center (NHIRC), Intramuros Administration's Father Luis Merino Library (FLM), Legislative Archives Service of House of Representatives (LAS), and The National Archives of the Philippines (NAP). The study was conducted to identify their overall mission/objectives; determine the criteria employed by archivists in appraisal; identify the external factors that affect the process; know the similarities and differences among the institutions when it comes to appraisal; and know the profile of the archivists or the personnel in charge of the archives.